Конструкторські методи зменшення шумів і завад у каналах із зосередженими параметрами при високошвидкісній обробці даних - Tynynyka, A. (PE "Politekhperiodika", Book and Journal Publishers, 2019)
The article is devoted to the methods and rules of electronic design of radio electronic devices, which provide high stability and electromagnetic compatibility. The author considers how interferences may be caused by the unsuccessful design decisions when constructing discrete-analog channels of information conversion. The paper gives practical recommendations for choosing appropriate element base, grounding and power sources. The urgency of these tasks is caused by the requirements for increasing the speed of semiconductor devices and electronic circuits in general and reducing the amplitude of the working signals of digital devices, as well as by the problems of increasing the impact of interconnections and the assembly of nodes on the stability and speed of electronic devices and systems, by the problems of reducing the production complexity, material and time consumption, and of finding and eliminating the causes of low noise immunity of electronic devices.With the growth of the speed and layout density of the elements, ensuring the immunity of the electromagnetic interaction between different devices and systems becomes the most important task in construing the radio electronic systems in general. When designing any electronic circuit, one should inevitably allow for addi¬tional parasitic parameters of resistive, inductive and capacitive nature, which may unacceptably impair the performance and noise immunity of the actual design, or even lead to complete loss of functionality. Design and installation have a particular effect on the work of super-high-speed (high frequency) circuits and de¬vices – here the provision of system speed, noise immunity and electromagnetic compatibility become the main criteria for the quality of electronic design.The analysis of the special characteristics of the element base and of the experience of designing power sources and grounding, should help the developers of the electronic devices to reduce the noise in the shaped channels of high-speed data processing.